2002
DOI: 10.1177/107602960200800404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Synthetic Factor Xa Inhibitor (JTV-803) on Various Laboratory Tests

Abstract: Synthetic direct inhibitors of factor Xa are capable of prolonging the global anticoagulant assay times in a concentration-dependent fashion. The relative degree of thrombin generation inhibition at an equivalent prolongation is not similar to the results observed with heparins and oral anticoagulant drugs. In addition, the direct factor Xa inhibitors prolong the Russell's viper venom test (RWT) and Heptest clotting times. Ecarin clotting time (ECT) and thrombin time (TT) remain unaffected. The kinetics of fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The PT assay has been widely used to monitor anticoagulant activity of warfarin (Kimmel 2008). However, it has been shown that PT is not a sensitive assay for Xa inhibition (Tobu et al 2002;Walenga and Hoppensteadt 2004;Paccaly et al 2006). The commercially available HCT employs exogenous bovine fXa as the activator.…”
Section: Discussionmentioning
confidence: 99%
“…The PT assay has been widely used to monitor anticoagulant activity of warfarin (Kimmel 2008). However, it has been shown that PT is not a sensitive assay for Xa inhibition (Tobu et al 2002;Walenga and Hoppensteadt 2004;Paccaly et al 2006). The commercially available HCT employs exogenous bovine fXa as the activator.…”
Section: Discussionmentioning
confidence: 99%
“…The HEMOCLOT assay is provided with dabigatran calibrators and yields a linear relationship (R = 0.99) with dabigatran concentrations from approximately 50 to 2000 ng mL )1 [20]. As the TT and dTT assays measure thrombin activity downstream from FXa, they are insensitive to the effects of FXa inhibitors [21]. Thus, although excessive concentrations of any of the new oral agents can prolong both the PT and APTT, the TT may help to identify which of the new anticoagulants is present; in the absence of confounding effects from multiple anticoagulants, a prolonged TT indicates dabigatran, whereas a normal TT is indicative of an FXa inhibitor.…”
Section: Dabigatranmentioning
confidence: 99%
“…17 It is partly attributable to the difference of assay reagents. 18,19 Administration of darexaban (60-240 mg qd) resulted in dose-dependent decreases in F 1þ2 levels, in contrast to no effect in the placebo group. This demonstrates that F 1þ2 can be used as a biomarker of darexaban's anticoagulant effect in future pivotal studies.…”
Section: Discussionmentioning
confidence: 99%